ChemInform Abstract: Organocatalytic Conjugate Addition of Nitroalkanes to 3‐Ylidene Oxindoles: A Stereocontrolled Diversity Oriented Route to Oxindole Derivatives. Issue 19 (13th May 2014) - Quintavalla, Arianna; Lanza, Francesco; Montroni, Elisa; Lombardo, Marco; Trombini, Claudio
Abstract The asymmetric Michael addition affords various substituted oxindole derivatives by using a thiourea‐based organocatalyst.